In vitro inhibition of phytopathogenic fungi using extracts of Mexican mistletoe (Psittacanthus calyculatus) - Xoca-Orozco, Luis Angel; Cortez-Fonseca, Karina; Luna-López, Carlos; Hernández-Mendoza, Gustavo; Flores-Sierra, José de Jesús; Chacón-López, Martina Alejandra; Aguilera-Aguirre, Selene (Ecosistemas y Recursos Agropecuarios, 2022)
Psittacanthus calyculatus is a hemiparasitic plant that affects various plant species of great importance to the ecosystem. Contains various compounds with antioxidant and antimicrobial activity. There are various reports on its antibacterial capacity; however, there is no information available on its antifungal activity. That is why the aim of this work was to show the antifungal activity of mistletoe extracts against the inhibition of Colletotrichum gloeosporioides, Fusarium sp. and Curvularia sp. For this, both mistletoe leaves and flowers obtained from two hosts were used: Prosopis laevigata and Eysenhardtia polystachya. The samples were washed, dehydrated and ground. Subsequently, a solid-liquid extraction was carried out using methanol-acetone-water. The content of phenols and flavonoids was quantified, as well as the phytochemical profile qualitatively. The evaluation of the antifungal activity was carried out with the plate dilution technique with PDA medium. The parameters of inhibition of mycelial growth, sporulation, germination was evaluated and the fungicidal or fungistatic effect was determined. The results showed an inhibition greater than 70% using both leaf and flower extracts, with Curvularia sp. being the most susceptible with 98% inhibition. There was also a reduction in sporulation and germination of the evaluated phytopathogens. It was determined that the inhibition corresponds to a fungistatic effect. The results reveal a high in vitro inhibition capacity of mistletoe extracts against phytopathogens of great importance for agriculture.